EFFECTS OF VARIED PACKAGES OF AQUATIC PLYOMETRIC TRAINING ON LEG EXPLOSIVE POWER AMONG COLLEGE MALE BASKETBALL PLAYERS (Journal of Pharmaceutical Negative Results, 2022)
The purpose of the study was to find out the effects of varied packages of Aquatic plyometric training on leg explosive power among college male basketball players. To achieve this purpose of the study, sixty basketball players of lovely professional University, (Punjab) were selected as subjects at random and their age were ranged between 18 to 23 years. The selected subjects were divided in to three equal groups of thirty subjects each. Group I underwent low intensity aquatic plyometric training, Group II underwent high intensity aquatic plyometric training for three days per week for twelve weeks. Group III acted as control that did not participate in any special training programme apart from their regular activities as per their curriculum. The following physical fitness components namely leg explosive power were selected as dependent variables. All the subjects of three groups were tested on selected dependent variables at prior to and immediately after the training programme. The analysis of covariance was used to analyze the significant difference, if any among the groups. Since, three groups were compared, whenever the obtained ‘F’ ratio for adjusted post test was found to be significant, the Scheffe’s test to find out the paired mean differences, if any. The .05 level of confidence was fixed as the level of significance to test the ‘F’ ratio obtained by the analysis of covariance, which was considered as an appropriate. . The result of the study indicates due to varied packages of aquatic plyometric training , leg explosive power max has been improved significantly.